2015
DOI: 10.1016/j.bbamcr.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin F2 receptor (FP) signaling regulates Bmp signaling and promotes chondrocyte differentiation

Abstract: Prostaglandins are a group of lipid signaling molecules involved in various physiological processes. In addition, prostaglandins have been implicated in the development and progression of diseases including cancer, cardiovascular disease, and arthritis. Prostaglandins exert their effects through the activation of specific G protein-coupled receptors (GPCRs). In this report, we examined the role of prostaglandin F2α receptor (FP) signaling as a regulator of chondrocyte differentiation. We found that FP expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Previous studies showed that PGF2α stimulated the expression of cartilage marker genes in a rat cell line and human articular chondrocytes [29,30]. Studies also revealed that PTGFR participates in chondrocyte hypertrophy differentiation by regulating Bmp signaling [27]. Therefore, PTGFR may affect hip joint development as a receptor of PGF2α, which promotes cartilage formation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies showed that PGF2α stimulated the expression of cartilage marker genes in a rat cell line and human articular chondrocytes [29,30]. Studies also revealed that PTGFR participates in chondrocyte hypertrophy differentiation by regulating Bmp signaling [27]. Therefore, PTGFR may affect hip joint development as a receptor of PGF2α, which promotes cartilage formation.…”
Section: Discussionmentioning
confidence: 96%
“…PTGFR, also known as FP, belongs to the G protein-coupled receptor family of seven transmembranespanning receptors. PTGFR plays an important role in chondrocyte differentiation and cartilage development [26][27][28]. PGF2α exerts its biological activities by binding to its receptor, PTGFR [29].…”
Section: Discussionmentioning
confidence: 99%
“…PTGFR (OMIM * 600563) , also known as FP, belongs to the G protein-coupled receptor family of seven transmembrane-spanning receptors. PTGFR plays an important role in chondrocyte differentiation and cartilage development [27][28][29]. PGF2α exerts its biological activities by binding to its receptor, PTGFR [30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, COX2 has been shown to regulate mesenchymal cell differentiation into osteoblast lineage [50]. We have also recently shown that prostaglandin F 2ɑ (PGF 2ɑ ) stimulates chondrocyte differentiation and promotes bone morphogenetic protein (BMP) signaling [51]. Thus, increased expression of COX2 may protect the skeleton from age-associated damage such as osteo-porosis, which is frequently observed in other mouse models of aging.…”
Section: Discussionmentioning
confidence: 99%